2022
DOI: 10.1093/ageing/afac263
|View full text |Cite
|
Sign up to set email alerts
|

A realist evaluation of a multifactorial falls prevention programme in care homes

Abstract: Background falls in care homes are common, costly and hard to prevent. Multifactorial falls programmes demonstrate clinical and cost-effectiveness, but the heterogeneity of the care home sector is a barrier to their implementation. A fuller appreciation of the relationship between care home context and falls programme delivery will guide development and support implementation. Methods this is a multi-method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Implementation of new protocols or guidance was the most common action taken by organisations in receipt of fall-related PFDs, but successful implementation of these changes is similarly important. Research demonstrates that success in reducing rates of falls in care homes is driven by effective staff-training to increase awareness of falls risk, local staff champions advocating an all-staff approach, and fostering attitudes that falls can be prevented [41]. A systematic review of falls prevention interventions in hospital inpatients found that patient and staff education in particular yielded significant reductions in falls rates [42], however previous reviews of guidelines have shown a relative paucity of education recommendations [43].…”
Section: Implications For Practicementioning
confidence: 99%
“…Implementation of new protocols or guidance was the most common action taken by organisations in receipt of fall-related PFDs, but successful implementation of these changes is similarly important. Research demonstrates that success in reducing rates of falls in care homes is driven by effective staff-training to increase awareness of falls risk, local staff champions advocating an all-staff approach, and fostering attitudes that falls can be prevented [41]. A systematic review of falls prevention interventions in hospital inpatients found that patient and staff education in particular yielded significant reductions in falls rates [42], however previous reviews of guidelines have shown a relative paucity of education recommendations [43].…”
Section: Implications For Practicementioning
confidence: 99%